Efficacy Of Guided Bone Regeneration (GBR) In Oral Reconstructive Procedures: An Original Research - Khanam, Fiza; Pathak, Nikita; Kumar, Ajay; Pareek, Shubhangi; Raheja, Anjali; Kumar, Ajay (Journal of Neonatal Surgery, 2025)
ABSTRACT Aim To evaluate the efficacy of Guided Bone Regeneration (GBR) in promoting alveolar bone regeneration in oral reconstructive procedures, with a focus on bone volume gain, implant success rates, and the overall clinical and aesthetic outcomes in patients requiring alveolar ridge augmentation. Method This study is a prospective clinical study aimed at evaluating the efficacy of Guided Bone Regeneration (GBR) in patients undergoing oral reconstructive procedures. It focuses on assessing bone volume gain, implant success rates, and clinical outcomes following GBR.A total of 30 patients (15 males and 15 females), aged between 20 and 60 years, were selected for this study. All patients presented with alveolar bone deficiencies requiring augmentation for future dental implant placement. Result The review showed that GBR significantly enhances bone regeneration in deficient alveolar ridges, with high implant survival rates (90–95%). Both resorbable and non-resorbable membranes were effective, though non-resorbable types offered greater space maintenance. Combining GBR with bone grafts, especially autogenous grafts, improved bone volume and quality. Membrane exposure was the most common complication but was manageable with proper technique. Conclusion Guided Bone Regeneration is a reliable and effective technique for restoring bone volume in oral reconstructive procedures, particularly for implant site development. Success depends on proper case selection, membrane type, and graft material. Despite some risks, GBR remains a cornerstone in modern implant dentistry.